A-Frame as a Tool to Create Artistic Collective Installations in Virtual Reality - João Azevedo (Proceedings, 2020)
Virtual Reality, due to its complexity and technological requirements, has a set of frictions that hinder its dissemination. The main ones can be summarized in the requirement to learn complex developing environments, like game engines, then we need to install applications, specific to each operating system and according to the means through which they can be accessed.